2016
DOI: 10.1007/s13213-016-1240-4
|View full text |Cite
|
Sign up to set email alerts
|

Bioreduction of hexavalent chromium by Pseudomonas stutzeri L1 and Acinetobacter baumannii L2

Abstract: Bioreduction of the very toxic hexavalent chromi- um ion [Cr(VI)] to the non-toxic trivalent chromium ion [Cr(III)] is a key remediation process in chromium- contaminated sites. In this study, we investigated the bioreduction of Cr(VI) by Pseudomonas stutzeri L1 and Acinetobacter baumannii L2. The optimum pH (5–10), tem- perature (27, 37 and 60 °C) and initial chromium Cr(VI) concentration (100–1000 mg L−1) for Cr(VI) reduction by strains L1 and L2 were determined using the diphenylcarbazide method. In the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…M6 had a 45.9% removal at 200 mg/L Cr(VI) concentration, but the Cr(VI) concentration in the control did not change signi cantly(Li et al 2019). It has been reported that Pseudomonas stutzeri L1 and Acinetobacter baumannii L2 strains reduce Cr(VI) by 40-97% and 84-99%, respectively, at concentrations of 100-1000 mg/L(Sathishkumar et al 2017). When we look at the studies on Cr(VI) removal with recombinant strains; as a result of the cloning of the ChrA, ChrB and ChrAB genes associated with Cr(VI) resistance of Serratia sp.…”
mentioning
confidence: 86%
“…M6 had a 45.9% removal at 200 mg/L Cr(VI) concentration, but the Cr(VI) concentration in the control did not change signi cantly(Li et al 2019). It has been reported that Pseudomonas stutzeri L1 and Acinetobacter baumannii L2 strains reduce Cr(VI) by 40-97% and 84-99%, respectively, at concentrations of 100-1000 mg/L(Sathishkumar et al 2017). When we look at the studies on Cr(VI) removal with recombinant strains; as a result of the cloning of the ChrA, ChrB and ChrAB genes associated with Cr(VI) resistance of Serratia sp.…”
mentioning
confidence: 86%
“…M6 had a 45.9% removal at 200 mg/L Cr(VI) concentration, but the Cr(VI) concentration in the control did not change signi cantly(Li et al 2019). It has been reported that Pseudomonas stutzeri L1 and Acinetobacter baumannii L2 strains reduce Cr(VI) by 40-97% and 84-99%, respectively, at concentrations of 100-1000 mg/L(Sathishkumar et al 2017). When we look at the studies on Cr(VI) removal with…”
mentioning
confidence: 99%
“…Therefore, during cleanup of soil from toxic Cr(VI) compounds, it is optimal to convert it into insoluble and non-toxic hydroxide directly in soils, because moisture and microbial exometabolites are unable to mobilize it. For example, Pseudomonas stutzeri was able to reduce Cr(VI) compounds (Sathishkumar et al, 2017). Bacillus brevis was resistant to elevated Cr(VI) levels and may potentially reduce it in short time from in the environment where other metal ions are also present in addition to chromium ions (Verma et al, 2009).…”
Section: Discussionmentioning
confidence: 99%